Longer looking to agent with false belief at 7 but not 6 months of age. Issue 5 (1st August 2021) - Hirshkowitz, Amy; Rutherford, M.D.
Abstract: Theory of mind refers to the ability to reason about others' beliefs and to understand others' behaviour in terms of those beliefs. A large body of previous research has examined theory of mind reasoning in young children using false belief tasks, but tasks to examine this capacity during infancy have only been developed more recently. This research used stimuli developed by Kovács, et al., Science, 2010, 330, 1830–1834, to measure looking time to an agent with a false belief in infants aged 6 and 7 months. Using an eye‐tracking procedure, we found looking behaviour consistent with 7‐month‐olds distinguishing an agent who has a false belief from one who has a true belief, consistent with the results reported by Kovács et al. We did not find evidence of this looking preference among 6‐month‐olds.